Strength behaviour of coal bottom ash self-compacting concrete exposed to cyclic wtting-drying in seawater - Hamzah, Ahmad Farhan; Fadzil, Norzubaidah; Wan Ibrahim, Mohd Haziman; Jamaluddin, Norwati; Putra Jaya, Ramadhansyah; Arshad, Mohd Fadzil; Zainal Abidin, Norul Ernida; Dahalan, Nurol Huda (Medwell Journals, 2017)
This study presents the strength behaviour of the self-compacting concrete which incorporated the coal bottom ash that was exposed to cyclic wetting and drying processes under the condition of seawater environment. The mixtures were produced by combining 0.40 water/powder ratio and coal bottom ash in varying percentages of 0, 10, 15, 20, 25 and 30%. The samples arising from each mixture were exposed to seawater environment with an average of 15 h of wetting process and 9 h of drying process per day. Consequently, the compressive strength behaviour of the concrete at the durations of 28, 60, 90 and 180 days under curing process were observed to understand the physical mechanisms that affected the concrete during the cyclic wetting and drying phases while exposed to harsh environments. The results of the cyclic wetting and drying processes in the laboratory indicated that there were significant strength reductions across all mixtures. It was found that that the strength of 10% coal bottom ash replacement sample is slightly higher than the control samples.